2010
DOI: 10.1021/la100822s
|View full text |Cite
|
Sign up to set email alerts
|

Hydrostatic Optimization of Inkjet-Printed Films

Abstract: In this work, we study the optimization of the geometry of inkjet-printed polymer films and develop a simple analytic framework to understand our results and establish limitations on inkjet-printed patterns. We show how drop spacing and ink concentration affect the thickness of a printed film and how hydrostatic conditions with contact angle hysteresis have to be considered to print optimized rectangular features. If advancing and receding contact angle are not taken into account, printed features will either … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
46
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 11 publications
1
46
0
Order By: Relevance
“…76 Soltman et al also showed that proper drop registration scheme can help preserve the pattern definition of the printed liquid films (Fig. 5), [76][77][78] and the receding contact angles of liquids on the substrate surfaces are of crucial importance to the accuracy of printed features. 79 With the addition of co-solvent adjustments, one can also adjust the contact angles to preserve the pattern definition.…”
Section: Printing Procedures Issuesmentioning
confidence: 99%
“…76 Soltman et al also showed that proper drop registration scheme can help preserve the pattern definition of the printed liquid films (Fig. 5), [76][77][78] and the receding contact angles of liquids on the substrate surfaces are of crucial importance to the accuracy of printed features. 79 With the addition of co-solvent adjustments, one can also adjust the contact angles to preserve the pattern definition.…”
Section: Printing Procedures Issuesmentioning
confidence: 99%
“…Although inkjet is a simple, non-contact direct-write method, it is usually limited to the transfer of low viscosity, chemically benign nanoparticle suspensions in order to avoid clogging and/or corrosion of the dispensing nozzles. In addition, printing patterns with well-defined edge features by inkjet is very difficult given the variable behavior of fluids on different surfaces and their resulting instability due to wetting effects 13 . Regardless, inkjet has enjoyed the most attention from researchers thus far.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason it has received increasing attention in the biotechnological and pharmaceutical fields since it enables performing complex analysis on small amounts of material, which are often expensive or in limited supply. A frequent issue in dispensing biological solutions onto flat substrates deals with control of size, shape and relative distance of dots as well as alignment and regularity of realized micro-arrays which occurs when spots are formed with a large number of droplets [11]. As a solution, preliminary micro-patterning of the substrate has been proposed [12].…”
Section: Introductionmentioning
confidence: 99%